1986
DOI: 10.1111/j.1365-2621.1986.tb01926.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative immunoassay for soya protein in raw and sterilized meat products

Abstract: An enzyme-linked immunosorbent assay (ELISA) is described for the quantitative analysis of soya protein in meat products. The assay is applicable to raw and sterilized products and is not dependent on soya variety and type of soya ingredient (concentrate, isolate, etc.). Therefore, the assay can be applied without knowledge of product composition, heat pretreatment and other processing conditions. The ELISA is specific for soya; no interference of other product components has been found. The detection limit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the second group, soya was detected in all model samples containing different types of soya additive (texturate, concentrate, soya flour, isolate). It was confirmed that immunochemical methods can be used for the detection of different kinds and types of soya protein (Ravestein & Driedonks 1986;Yasumoto et al 1990). …”
Section: Comparison Of the Results With The Confirmation Methodsmentioning
confidence: 88%
“…In the second group, soya was detected in all model samples containing different types of soya additive (texturate, concentrate, soya flour, isolate). It was confirmed that immunochemical methods can be used for the detection of different kinds and types of soya protein (Ravestein & Driedonks 1986;Yasumoto et al 1990). …”
Section: Comparison Of the Results With The Confirmation Methodsmentioning
confidence: 88%
“…Previous studies have detected soybean proteins by using ELISA based on antibodies to soybean proteins such as the trypsin inhibitor 7S‐conglycinin and 11S glycinin (Hitchcock and others ; Ravestein and Driedonks ; Brandon and others ; Koppelman and others ). However, to our knowledge there have been no reports of the successful detection of soybean proteins in fermented soybean products.…”
Section: Resultsmentioning
confidence: 99%
“…Another alternative was indirect determination of soy protein content using the quantification of the phytic acid content, which is bound to plant proteins 50 . Studies describing the use of immunological analysis for the detection and quantification of plant proteins in meat products have also been reported 51,52,53,54,55 .…”
Section: Determination Of Soybean Protein Inmentioning
confidence: 99%